DINÂMICAS MERCANTIS COLONIAIS : Capitania do Rio Grande do Norte (1760-1821) - Dias, Thiago Alves (2011)
The size and dynamics of the market producer, consumer and exporter of the Captaincy of Rio Grande do Norte, in the period between 1760 and 1821 is the primary goal of this dissertation. In order to establish relations between the founding of new towns built from 1750 and its incorporation into the water supply and domestic market, showing more specifically the colonial economic relations established between the coast and the hinterland of the Province. Based on references by authors such as Edward Shils and Immanuel Wallerstein have investigated topics such as formation of colonial space, deployment-action of colonial institutions regarding business practices, and the dynamic market of the Province of Rio Grande do Norte.